Substance P increases liver fibrosis by differential changes in senescence of cholangiocytes and hepatic stellate cells. Issue 2 (19th June 2017) - Wan, Ying; Meng, Fanyin; Wu, Nan; Zhou, Tianhao; Venter, Julie; Francis, Heather; Kennedy, Lindsey; Glaser, Trenton; Bernuzzi, Francesca; Invernizzi, Pietro; Glaser, Shannon; Huang, Qiaobing; et al.
Abstract : Substance P (SP) is involved in the proliferation of cholangiocytes in bile duct–ligated (BDL) mice and human cholangiocarcinoma growth by interacting with the neurokinin‐1 receptor (NK‐1R). To identify whether SP regulates liver fibrosis during cholestasis, wild‐type or NK‐1R knockout (NK‐1R –/– ) mice that received BDL or sham surgery and multidrug resistance protein 2 knockout ( Mdr2 –/– ) mice treated with either an NK‐1R antagonist (L‐733, 060) or saline were used. Additionally, wild‐type mice were treated with SP or saline intraperitoneally. In vivo, there was increased expression of tachykinin precursor 1 (coding SP) and NK‐1R in both BDL and Mdr2 –/– mice compared to wild‐type mice. Expression of tachykinin precursor 1 and NK‐1R was significantly higher in liver samples from primary sclerosing cholangitis patients compared to healthy controls. Knockout of NK‐1R decreased BDL‐induced liver fibrosis, and treatment with L‐733, 060 resulted in decreased liver fibrosis in Mdr2 –/– mice, which was shown by decreased sirius red staining, fibrosis gene and protein expression, and reduced transforming growth factor‐β1 levels in serum and cholangiocyte supernatants. Furthermore, we observed that reduced liver fibrosis in NK‐1R –/– mice with BDL surgery or Mdr2 –/– mice treated with L‐733, 060 was associated with enhanced cellular senescence of hepatic stellate cells and decreased senescence of cholangiocytes. In vitro, L‐733, 060 inhibited SP‐induced expression of fibrotic genes in hepatic stellate cells and cholangiocytes; treatment with L‐733, 060 partially reversed the SP‐induced decrease of senescence gene expression in cultured hepatic stellate cells and the SP‐induced increase of senescence‐related gene expression in cultured cholangiocytes. Conclusion : Collectively, our results demonstrate the regulatory effects of the SP/NK‐1R axis on liver fibrosis through changes in cellular senescence during cholestatic liver injury. (Hepatology 2017;66:528–541).